Training Teachers To Use Action Research In The Classroom - Arsen Nahum Pasaribu; Sondang Manik; Erika Sinambela; Tiara K Pasaribu; Jubil Ezer Sihite; Rony Arahta Sembiring; Febrika Dwi Lestari; Ance Juliet Panggabean (International Journal Of Community Service, 2021)
Teachers are trained in senior high schools to increase their competence in designing and implementing CAR in the classes they teach. Seven students and eight teachers from SMAN 2 Panyabungan made up the training participants for this course. On the first day, CAR planning was stressed, and on the second day, CAR implementation was detailed. The community service was conducted by 8 lecturers of Universitas HKBP Nommensen Medan, on March 5-6, 2021. The results show that teachers' understanding of the CAR cycle had increased, however they required additional training to improve their ability to collect data and do data analysis techniques.